2018
DOI: 10.1302/1863-2548.12.180123
|View full text |Cite
|
Sign up to set email alerts
|

Selective dorsal rhizotomy in ambulant children with cerebral palsy

Abstract: Abstract:BackgroundSelective dorsal rhizotomy (SDR) is a surgical procedure for treating spasticity in ambulant children with cerebral palsy (CP). However, controversies remain regarding indications, techniques and outcomes.Current evidence summaryBecause SDR is an irreversible procedure, careful patient selection, a multi-disciplinary approach in assessment and management and division of the appropriate proportion of dorsal rootlets are felt to be paramount for maximizing safety. Reliable evidence exists that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
0
24
1
1
Order By: Relevance
“…Prior research on the impact of SDR on energy consumption has also reported reductions in energy, but compared to a control group of TD peers or no control group (Carraro et al, 2014;Nicolini-Panisson et al, 2018;Wang et al, 2018). For example, Trost and colleagues (2008) reported a 22% reduction in energetic cost after SDR (Trost et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on the impact of SDR on energy consumption has also reported reductions in energy, but compared to a control group of TD peers or no control group (Carraro et al, 2014;Nicolini-Panisson et al, 2018;Wang et al, 2018). For example, Trost and colleagues (2008) reported a 22% reduction in energetic cost after SDR (Trost et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Selective dorsal rhizotomy (SDR) is a neurosurgical procedure where afferent nerve fibers in dorsal rootlets are cut to reduce efferent excitations (Tedroff et al, 2011). SDR has been shown to significantly reduce spasticity (Wang et al, 2018). Prior outcome studies have also suggested that SDR reduces energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…• continuous intrathecal infusion of baclofen through a pump • selective dorsal rhizotomy: cutting of 50-75% of the dorsal (afferent) nerve fibres on L1-S1 level; this treatment has a permanent and irreversible effect, reducing spasticity solely in the lower limbs • selective peripheral neurotomy: cutting some of the fibres of the peripheral nerve innervating a particular muscle/group of muscles; it only affects the spasticity of the muscle innervated by the cut nerve fibres. [87][88][89] Additional problems in cerebral palsy, such as gastroesophageal reflux, nutrition disorders, and constipation, require the use of specialist therapy methods, which are frequently surgical treatments. Most recently, the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) published guidelines for the evaluation and treatment of gastrointestinal and nutritional complications in children with neurological impairment.…”
Section: Treatment Of Motor Disorders In Cpmentioning
confidence: 99%
“…2,3 However, the indications have been stretched to many different patient populations including those with dystonia and dyskinesia, including non-ambulatory patients. When the appropriate patients with the appropriate indications are chosen, there have been positive results in terms of patient reported outcomes and improvement in function.…”
mentioning
confidence: 99%
“…When the appropriate patients with the appropriate indications are chosen, there have been positive results in terms of patient reported outcomes and improvement in function. 2,3 However, the indications have been stretched to many different patient populations including those with dystonia and dyskinesia, including non-ambulatory patients. 4 One of the post-SDR complications is weakness with increased pelvic tilt and Trendelenburg gait.…”
mentioning
confidence: 99%